'Kult' i religionsvidenskab og arkæologi - Christensen, Lisbeth Bredholt (Religionsvidenskabeligt Tidsskrift, 2004)
The word 'cult' is only rarely used in the Study of Religion today, whereas, instead, 'religion', 'ritual' and 'religious practice' are used. in Prehistoric and Classical Archaeology, as well as in Ancient History, however, 'cult' is a common term. The connotations of the word 'cult' differ among various disciplines. In Prehistoric Archaeology, 'cult' denotes 'religious retual' or the practical aspect os 'religion, i.e. the use of 'cult' (unjustifiably, according to the present author) appears to make it possible for prehistorians to speak about religion without takin into consideration 'belief' (not visible in the aarchaeological material). In Classical Archaeology and Ancient History 'cult' is not in the same way a terminus techicus because it is found in the texts. In these disciplines 'cult' is used as a synonym for 'religion', emphasizing that in Greek and Roman societies 'religion' is based on worshipping gods and heroes, but not necessarily involving belief. in Socioloy, 'cult' has been assigned a completely independent measning, possibly deriving from 'mystery-cult'. In the Study of Religion the attempts at defining and discussing 'cult' are limited to studies of ancient Israel, early Christianity, ancient Near East and the classical world. Various attempts have been made to use 'cult' as an abstract, universally applicable concepts in the same fashion as 'ritual' and 'religion'. However, these attempts seem to have been ony partially successful. Ultimately, 'cult' is a very vague word lingering between the abstract and theoretical on the one hand and, on the other hand, remaining fixed in the regional and chronological context of the ancient Mediterranean and Near East worlds.